Comparative study of IUCD inserted intracesarean and after vaginal delivery - Goyal, Archana; Wadhwani, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In view of high rate of unintended pregnancy in our country, particularly in post-partum women, there is a need for reliable, effective, long-term contraception such as intrauterine device (IUD) in post-partum women. The present study was planned to evaluate the safety and efficacy of immediate post-partum IUD insertion in women delivering vaginally or by caesarean section. Methods: The women recruited had CuT 380A insertion immediately after delivery of placenta in vaginal or caesarean delivery. Women having post-partum haemorrhage (PPH), anaemia, pre-labour rupture of membranes >18 h, obstructed labour and distorted uterine cavity by fibroid or by congenital malformation were excluded from the study. The women were followed up at 6 weeks after delivery. Results: A total of 500 women were included in the study. The present study shows that expulsion rate was more in postplacental insertion group i.e. 13.2% while among intracaesarean group it was 6.8% and this difference was statistically significant. Removal rate of PPIUCD (Post-partum Intrauterine Contraceptive device) was higher in postplacental insertion i.e.43 (17.2%) cases whereas in intracaesarean insertion removal rate was 8.4%. Most common cause of removal of PPIUCD in our study was pelvic pain and menstrual disturbances. Conclusions: Thus, from our study it is concluded that PPIUCD is safe, convenient, cost effective, reversible and long-term birth spacing method. It should be part of a maternal/newborn/reproductive health package.